2001
DOI: 10.1530/eje.0.1450161
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase is not activated in human hyperplastic and adenomatous parathyroid tissue

Abstract: Background: Telomerase is a speci®c enzyme that appears to have a key role in cellular senescence and the progression of neoplastic tissue. High telomerase activity has been found in several cancers, but not in most normal and benign tissue. Little is known about the in¯uence of telomerase on the abnormal growth associated with hyperparathyroidism. Objective: To analyse telomerase activity in parathyroid tissue obtained from 29 patients undergoing surgery for primary hyperparathyroidism. Design: Tissue for tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Results of this real-time PCR method are expressed as a C T value representing the suggested that TA was not involved in the abnormal growth of cells with hyperparathyroidism. 12 Two other reports and our results concurred with these observations. Thus, we suggest that TA is present only in malignant parathyroid tumors.…”
Section: Real-time Pcr Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Results of this real-time PCR method are expressed as a C T value representing the suggested that TA was not involved in the abnormal growth of cells with hyperparathyroidism. 12 Two other reports and our results concurred with these observations. Thus, we suggest that TA is present only in malignant parathyroid tumors.…”
Section: Real-time Pcr Analysissupporting
confidence: 93%
“…12 Total RNA was collected from samples, using a TRI-reagent (Life Technologies, Gaithersburg, MD, USA). One nanogram of total RNA was reverse-transcribed in a 20-µl reaction buffer, containing 1 µl (0.…”
Section: Reverse Transcription (Rt)-pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…(1999) reported finding that metastatic tissue from primary parathyroid carcinoma and primary cultured cells from only one patient with a parathyroid carcinoma exhibited a very high telomerase activity according the results of a telomeric repeat amplification protocol (TRAP) assay. Velin et al . (2001) reported that normal, hyperplastic and adenomatous parathyroid tissue were telomerase negative.…”
mentioning
confidence: 99%
“…By contrast, telomerase activity was virtually absent in adenomas (0/47), hyperplasias (0/11), and normal parathyroid tissues (0/23) (Falchetti et al 1999, Velin et al 2001, Kammori et al 2003, Onoda et al 2004. These observations suggest that telomerase activation is necessary for parathyroid malignancy but not for the proliferation of benign lesions.…”
Section: Endocrine-related Cancermentioning
confidence: 93%